Reflections on Research Performance Measures and the Rise of Asia - Pendlebury, David (International Higher Education, 2010)
Citations in the journal literature are reliable indicators of influential ideas. Citation indexes enable retrieval and analysis of information regarding most cited papers. Citation analysis provides un understanding of thorough performance regarding influential nations, institutions, research groups, and even individual scientists. In the share of science publications, the U.S. and Western Europe have declined from 1981 to 2008 while Asia is rising in academic performance; Japan is still strong, Singapore emphasizes quality, India boosts output, and China shows a remarkable rise.